Stopping the Traffick? The problem of evidence and legislating for the ‘Swedish model’ in Northern Ireland - Huschke, Susann; Ward, Eilís (Anti-Trafficking Review, 2017)
In 2015, after two years of controversy, the so-called ‘Swedish model’—the criminalisation of paying for sex—became law in Northern Ireland as an anti-trafficking measure. Evidence from the ground in Northern Ireland, however, questions the enforceability and appropriateness of a sex purchase ban to significantly reduce or eradicate trafficking in the sex industry. First, it is unclear that criminalisation will change the behaviour of male purchasers, many of whom thought that their actions were already illegal; second, sex workers do not support the law; and third, there are significant difficulties in law enforcement in the context of Northern Ireland, including a lack of police resources. This article examines mitigating evidence drawn from two sources: findings from a mixed methods study commissioned by the Department of Justice of Northern Ireland—in which we were amongst several co-authors—to support the reform process; and contributions to the consultation held within it. We argue that the sex purchase ban in Northern Ireland is essentially meant to send a moral message about the unacceptability of commercial sex rather than effectively reduce trafficking. With this conclusion, we aim to contribute to an open and honest debate about the moral foundations of anti-trafficking measures, the role of research evidence in the policy process, and the gap between stated intentions and likely effects of neo-abolitionist measures such as the sex purchase ban in both Northern Ireland and more generally.